Access to Urban Land and its Role in Enhancing Business Environment: Multi-track versus Mono-route Land-use Markets - Stebek, EN (Mizan law review, 2015)
Access to urban land for business activities relates to access to working space, or using and/or controlling a unit of land based on open access, land ownership, land lease, business lease or premise rentals. Diversified and broad-based access to urban land with due regulatory control against speculation and holdouts enhances the dynamism and competitiveness of business activities, while on the contrary, mono-route land use markets such as municipal control of urban land provision suppresses the supply and transferability of land use rights thereby creating land use market imperfections. This article discusses the role of access to urban land and its transferability in enhancing the business environment, inter alia, as one of the major inputs in the production of goods and services. Rising urban population and correspondingly increasing business activities lead to urban intensification and urban frontier expansion to adjacent rural areas which should be addressed with prudence and caution in the context of accurate land information, efficient utilization of urban land, effective and transparent land governance and due attention to good practices in comparative legal regimes. Key terms: Access to urban land, business environment, urban land law, urban intensification, urban extensions, informal settlements, Ethiopia.